Relationship between knowledge, attitudes and hygiene practices in food handlers in kiosks of Public Educational Institutions of Ate, 2017 - García Loyaga, Geordy Holmes (2018)
Objective: This research aims to determine the relationship among knowledge, attitude and practice about hygiene in food handlers who work in stalls of Public Schools in Ate, Methodology: This study is a qualitative approach of transversal cut, of non-experimental design and correlacional type. The partipants were formed by the 145 food handlers of the 70 different stalls that are in the schools in Ate. the instrument used was a quiestionnaire about hygiene knowledge and attitude from the food handlers and a practice verification form. Results: The results showed that 78.6% of participants presented a high level in hygiene knowledge, and 87.6% presented a favorable level of hygiene attitude, while 73% of the food handlers presented appropiate food hygiene practices. In respect with the correlation between hygiene knowledge and attitude of food handlers, using the test of Spearman Rho, it was demonstrated that statistically, there is a significant correlation (p<;05) between them. In addition, it was evidenced that there is a statistical significant correlation between hygiene knowledge and practice from food handlers (p<;05); it is also observed that there is no statistically significant correlation between the attitude of food handlers and their practices (p>.05). Conclusions: In conclusion, food handlers have knowledge, attitude and appropriate practices on food hygiene, in most of the areas that were requested.